A Rare KIF1A Missense Mutation Enhances Synaptic Function and Increases Seizure Activity - Guo, Yi; Chen, Yuanyuan; Yang, Min; Xu, Xin; Lin, Zijun; Ma, Junhong; Chen, Hongnian; Hu, Yida; Ma, Yuanlin; Wang, Xuefeng; Tian, Xin (Frontiers in Genetics, 2020)
Although genetic factors are considered a main etiology of epilepsy, the causes of genetic epilepsy in the majority of epilepsy patients remain unknown. Kinesin family member 1A (KIF1A), a neuron-specific motor protein that moves along with microtubules, is responsible for the transport of membranous organelles and synaptic vesicles. Variants of KIF1A have recently been associated with hereditary spastic paraplegia (HSP), hereditary sensory and autonomic neuropathy type 2 (HSANII) and intellectual disability. However, mutations in KIF1A have not been detected in patients with epilepsy. In our study, we conducted customized sequencing of epilepsy-related genes of a family with six patients with generalized epilepsy over three generations and identified a rare heterozygous mutation (c.1190C>A, p. Ala397Asp) in KIF1A. Whole-cell recordings from primary cultured neurons revealed that the mutant KIF1A increases the excitatory synaptic transmission but not the intrinsic excitability of neurons, and phenotype testing in zebrafish showed that this rare mutation results in epileptic seizure-like activity. These results provide new evidence demonstrating that KIF1A dysfunction is involved in epileptogenesis.